2017
DOI: 10.1111/jcpt.12611
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilia secondary to lenalidomide therapy

Abstract: Eosinophilia has rarely been described with lenalidomide. This case shows a clear temporal relationship between lenalidomide and eosinophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Nurrochmad et al observed that CD8 + T cells in peripheral blood were reduced by CTX treatment (150 and 100 mg/kg body weight on days 1 and 4) [ 31 ]. Escudero-Vilaplana reported that CTX caused increase in eosinophils [ 32 ]. Wu et al demonstrated that CTX treatment (140 mg/kg every 6 days) induced reduction of CD8+ T cells in blood while increasing CD8+ T-cell infiltration into tumors [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nurrochmad et al observed that CD8 + T cells in peripheral blood were reduced by CTX treatment (150 and 100 mg/kg body weight on days 1 and 4) [ 31 ]. Escudero-Vilaplana reported that CTX caused increase in eosinophils [ 32 ]. Wu et al demonstrated that CTX treatment (140 mg/kg every 6 days) induced reduction of CD8+ T cells in blood while increasing CD8+ T-cell infiltration into tumors [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 Palonosetron hydrochloride (INN, trade name Aloxi), for example, is a 5-HT3 receptor antagonist indicated for the prevention and treatment of chemotherapy-induced nausea and vomiting (CINV). 8 Isoindolinones, or benzofused γ-lactams, are another class of natural products, 9 and are found in the NSAID anti-inflammatory indoprofen, 10 multiple myeloma treatment lenalidomide 11 and antiplatelet drug indobufen. 12 In addition, N -acyl sulfonamides are best known as bacteriostatic and antimalarial agents and are also present in a range of drugs possessing various pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%